2011
DOI: 10.1097/sla.0b013e318203a289
|View full text |Cite
|
Sign up to set email alerts
|

Selective Reduction in Neural Responses to High Calorie Foods Following Gastric Bypass Surgery

Abstract: Objective To investigate changes in neural activation and desire to eat in response to appetitive cues from pre- to postbariatric surgery for obesity. Background Roux-en-Y gastric bypass (RYGB) is the most common bariatric procedure. However, the mechanisms of action in RYGB are not well understood. A significant proportion of the resulting reduction in caloric intake is unaccounted for by the restrictive and malabsorptive mechanisms and is thought to be mediated by neuroendocrine function. Numerous investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

25
213
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(243 citation statements)
references
References 45 publications
(85 reference statements)
25
213
3
1
Order By: Relevance
“…Postoperative neuroendocrine alterations are suggested to play an important role in these effects of RYGB (21). Decreased activations in areas that are part of the central reward circuits (among others, ventral striatum and putamen) in response to visual food cues after RYGB have been described (6,7). RYGB is also associated with a deceased desire to eat highly palatable food (6,22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Postoperative neuroendocrine alterations are suggested to play an important role in these effects of RYGB (21). Decreased activations in areas that are part of the central reward circuits (among others, ventral striatum and putamen) in response to visual food cues after RYGB have been described (6,7). RYGB is also associated with a deceased desire to eat highly palatable food (6,22).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased activations in areas that are part of the central reward circuits (among others, ventral striatum and putamen) in response to visual food cues after RYGB have been described (6,7). RYGB is also associated with a deceased desire to eat highly palatable food (6,22). In accordance with these studies, we observed decreased CNS activation in response to both visual and gustatory food cues after RYGB, paralleled by decreased scores for hunger and appetite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Bruce et al (39) reported that patients who had undergone gastric banding surgery showed higher inferior frontal activity during the processing of food pictures before than after surgical intervention. In addition, changes in food reward-related brain regions were reported soon after bariatric surgery (24) and after a weight loss of at least 8% (40). The globus pallidus is proposed to directly initiate reward-related signals (41).…”
Section: Discussionmentioning
confidence: 99%
“…On a neuronal level, bariatric surgery results in altered neuronal responses to food cues, particularly in the reward, gustatory, and homeostatic regions (11,(24)(25)(26). A comparison of neuronal responses to food items between patients postsurgery and a lean and an obese control group showed that severely obese women who underwent RYGB at least 1 year earlier showed a normalization of obesity-associated alterations in brain activity (25).…”
mentioning
confidence: 99%